Performance of semi-autonomous public bodies: linkages between autonomy and performance in Japanese agencies - Yamamoto, Kiyoshi (2006)
The creation of semi-autonomous public bodies or agencification has been diffused around the world. The basic concept lies in giving more autonomy in operations in exchange for strengthening accountability for results. It is assumed that granting more flexibility in management produces more efficient and effective outcomes. However, the causal relationship between autonomy and performance has been inconclusive despite many empirical studies. This is because institutional factors are neglected, as are other measurement problems such as using cross-section data. Consequently, in this article, the relationship is examined using institutional factors and a retrospective survey method to study Japanese agencies. The analysis shows that there is a causal relationship between operational autonomy and performance but only partial causal linkages between other types of autonomy like structural or legal autonomy and performance. - Reproduced.
Keywords: Administrative reform - Japan; Administrative reform